2017
DOI: 10.1093/cid/cix113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Carbapenem-Resistant Enterobacteriaceae Among Adult Inpatients in Singapore

Abstract: Background. Since 2010, the incidence of carbapenem-resistant Enterobacteriaceae (CRE) has been increasing in Singapore. We analyzed the clinical and molecular epidemiology of CRE among adult inpatients in Singapore.Methods. Quarterly incidence of unique subjects (per 100 000 patient-days) with positive clinical and surveillance cultures for CRE were estimated based on mandatory data submitted to the National Public Health Laboratory by public hospitals between 2010 and 2015. CRE-positive adult inpatients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 23 publications
(18 reference statements)
1
57
0
Order By: Relevance
“…During the 3-year surveillance period, high rates of carbapenem resistance and an increasing trend in the incidence of CRE in normally sterile site cultures, especially those caused by CRKP, were observed at Henan General Hospital. Rapid increases in the prevalence of CRE have been reported globally (8,9,19). In Singapore, a sharp increase in the incidence of clinical CRE infections was observed between 2010 and 2011, resulting mainly from a lack of proper intervention (early identification and spatial separation) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 3-year surveillance period, high rates of carbapenem resistance and an increasing trend in the incidence of CRE in normally sterile site cultures, especially those caused by CRKP, were observed at Henan General Hospital. Rapid increases in the prevalence of CRE have been reported globally (8,9,19). In Singapore, a sharp increase in the incidence of clinical CRE infections was observed between 2010 and 2011, resulting mainly from a lack of proper intervention (early identification and spatial separation) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid increases in the prevalence of CRE have been reported globally (8,9,19). In Singapore, a sharp increase in the incidence of clinical CRE infections was observed between 2010 and 2011, resulting mainly from a lack of proper intervention (early identification and spatial separation) (19). A nationwide surveillance study of clinical CRE isolates in China from June 2014 to June 2015 indicated that 1.2 to 18.9% of K. pneumoniae isolates were resistant to carbapenems (20).…”
Section: Discussionmentioning
confidence: 99%
“…All seven government-funded multidisciplinary hospitals in Singapore, which provide Ͼ80% of inpatient medical care in Singapore, participated in this network. Interim results and the methodology of the prospective CaPES study have previously been published and showed that all major genotypes of CPE were endemic in Singapore (22).…”
Section: Methodsmentioning
confidence: 99%
“…Various mechanisms are involved in the development of carbapenem resistance depending on the bacterial species. However, since their discovery, carbapenemases (e.g., NDM, KPC, and OXA) have emerged as key drivers of carbapenem resistance across various Gram-negative bacterial species [2,3]. Lack of effective treatment and the consequent high mortality [4] has increased emphasis on the prevention of MDRGN transmission.…”
Section: Introductionmentioning
confidence: 99%